2010
DOI: 10.1590/s1516-14392010000300015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Experimental Denture Cleanser Solution Ricinus communis on Acrylic Resin Properties

Abstract: This study evaluated heat-polymerized (HPR) and microwave-polymerized acrylic resins (MPR), after immersion in water, 1% hypochlorite and Ricinus communis solution (RC). Knoop hardness, color alteration, roughness and flexural strength tests were performed after obtaining the specimens and after time intervals of 15 (T 15 ) and 183 (T 183 ) days. Variations in data (∆) were submitted to ANOVA and Tukey tests (P = 0.05). For ∆T 15HPR there was greater variation in hardness when immersed in water (P = 0.00)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(78 citation statements)
references
References 27 publications
4
48
1
25
Order By: Relevance
“…Davi et al evaluated continuous use of sodium hypochlorite for 8 hours, 1% over 6 months, showing a significant change in resin color (as in this study) and flexural strength, but without alteration in surface roughness, different from the results of this study, which showed change in roughness in all tested liquids, including water (control). Similar results were found in other studies showing a significant change in the roughness of acrylic resin immersed into solutions based on castor oil and propolis orobase gel …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Davi et al evaluated continuous use of sodium hypochlorite for 8 hours, 1% over 6 months, showing a significant change in resin color (as in this study) and flexural strength, but without alteration in surface roughness, different from the results of this study, which showed change in roughness in all tested liquids, including water (control). Similar results were found in other studies showing a significant change in the roughness of acrylic resin immersed into solutions based on castor oil and propolis orobase gel …”
Section: Discussionsupporting
confidence: 92%
“…Regarding Knoop microhardness, the results of this work showed no significant alterations in pink or colorless acrylic resin when evaluated until 12‐month immersion in any of the liquids tested. Pisani et al found different results by using 2% castor oil showing that there was a decrease of microhardness. da Silva et al, using alcoholic propolis gel extract, showed that microhardness increased over time.…”
Section: Discussionmentioning
confidence: 99%
“…The use of denture cleaning dentifrices is recommended since brushing using water alone does not remove organic deposits and stains from dentures (4). However, cleaning complete dentures using a soft bristled toothbrush combined with dentifrices was also associated with adverse effects on acrylic resin (32). The results of the present study revealed significant weight loss at 40,000 brushing strokes and at 60,000 strokes and the presence of small scratches following 60,000 strokes which may be due to the abrasive properties of the dentifrice used.…”
Section: Discussionmentioning
confidence: 99%
“…After this period, the color change, roughness and flexural strength tests were performed. The calculation of these immersion periods was done by the following method 24 .…”
Section: Immersion Periodmentioning
confidence: 99%